Parameter Influences on HVDC Transformer Insulation and Its Link to Conduction Processes - Schober, Fabian; Krieg, Andreas; Küchler, Andreas; Liebschner, Marcus; Berger, Frank (International Journal of Electrical and Computer Engineering Systems, 2015)
HVDC (high voltage direct current) transmission is an effective way to transport electrical power over long distances by using direct current. The insulation system of HVDC components has to be designed for both AC and DC field distributions. It consists of mineral oil and pressboard. The used insulation material behavior has not been completely understood under DC stress. In this paper, electrical conductivity of pressboard is evaluated and conduction processes are considered. Therefore, conductivity measurements are linked to a number of RC network elements in order to achieve a network model representative for the insulation material behavior under DC stress. Time-constants are determined under different temperatures and different electric field strengths. In addition, the performed simulations provide evaluation of parameters affecting the dielectric behavior of the insulation system oil and pressboard, which are not measured or even cannot be determined by measurements.